Correlation between Hemoglobin Reticulocytes and Ferritin in Chronic Kidney Disease Patients Undergoing Hemodialysis at PKU Bantul - Muhammad Salman Shalahuddin; Linda Rosita (Berkala Kedokteran, 2021)
Abstract: As many as 7 – 12% of the world's population has chronic kidney disease (CKD). CKD patients can experience various complications, one of which is anemia. Anemia can cause a variety of cardiovascular complications in CKD patients. Enforcement of the diagnosis of anemia and its type is carried out by laboratory examination, among others by examination of reticulocytes-hemoglobin (ret-he) and iron status such as serum ferritin. Examination of these parameters can help in planning the right treatment for CKD patients who have anemia. The purpose of this study was to determine the relationship of Ret-he with ferritin levels in CKD patients undergoing hemodialysis at PKU Bantul Hospital. This study used cross-sectional method. The data source used was secondary data obtained from medical records and the Indonesian Renal Registry (IRR). Sampling research used consecutive sampling method. The analysis used univariate analysis which was frequency distribution table, and bivariate analysis. Univariate analysis obtained that average levels of ret-he from 50 subjects was 28.87 ± 3.75 pg and median serum ferritin levels were 118,1 (9,76 – 1615) mL. Bivariate analysis with pearson correlation test found a significant correlation between serum ret-he and ferritin levels (r = 0.498, p = 0.000).There was a significant correlation between he-ret levels and serum ferritin levels Keywords: chronic kidney disease, anemia, reticulocytes-hemoglobin, serum ferritin.